Effect of sand temperature and feedstock feed rate on pyrolysis of imperata cyclindrica - Tay, Kian Soon, 1990-, author; Tuan Amran Tuan Abdullah, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2013